VALORACIÓN DEL RIESGO FAMILIAR EN FAMILIAS CON NIÑOS CON ANEMIA EN UNA POBLACIÓN MARGINAL EN LIMA NORTE - Matta Solis, Hernan Hugo (2020)
Objectives: To determine the assessment of family risk in families with children with anemia in a marginal population in North Lima. Materials and methods: The focus of this study was quantitative, descriptive-crosssectional design. The population was made up of 197 heads of families who had as a member at least one child under five years of age with anemia. The technique used was the survey and the measurement instrument was the RFT 5:33 Questionnaire. Results: As for the participants, the minimum age was 18 years and the maximum 48 years, the mean age being 23.66 years. Regarding the degree of anemia in children under 5 years of age, the mild level predominated with 56.9% (n = 112), followed by the moderate level with 39.6% (n = 78). According to the total family risk, families with low risk prevailed 56.9% (n = 112), followed by families threatened with 39.6% (n = 78) and families with high risk with 3.6% (n = 7). Regarding the dimensions, in health services and practices, families threatened predominated with 89.3% (n = 176); followed by the dimensions of housing and neighborhood conditions, socioeconomic situation and handling of minors, where threatened families prevailed with 87.8% (n = 173) in the three cases. Finally, in psycho-affective conditions, threatened families predominated with 84.3% (n = 166). Conclusions: Regarding family risk, low family risk predominated. In terms of dimensions, threatened families predominated in all of them.